Transforming Families through Free Tertiary Education Grants in the Philippines - OLAPANE, ELIAS C.; CONTRERAS, ROSARIO CLARABEL C.; QUINDIPAN, NELMA T. (Journal of Interdisciplinary Studies in Education, 2024)
Education is a basic right of every human being in many countries around the world. However, tertiary education has remained a challenge, especially for marginalized and vulnerable segments of society. This has prompted the Philippine government to implement a free tertiary education grant since 2013, known as the Expanded Students’ Grant-in-Aid Program for Poverty Alleviation (ESGP-PA), as a transformational force for impoverished yet academically inclined students to pursue and complete college. This qualitative case study was conducted to determine the social transformation that occurred among graduate-grantees and their families after they received free tertiary education in the Philippines. The results showed that the economic inadequacy of the participants served as a significant motivation for them to overcome academic and personal challenges, as did the support of their parents, friends, and strong faith in religion. Moreover, this free tertiary education program has emancipated the participants from the bondage of poverty, leading to improved socioeconomic conditions.